2010
DOI: 10.1105/tpc.110.077578
|View full text |Cite
|
Sign up to set email alerts
|

Structure-Function Analyses of a Caffeic Acid O-Methyltransferase from Perennial Ryegrass Reveal the Molecular Basis for Substrate Preference  

Abstract: Lignin forms from the polymerization of phenylpropanoid-derived building blocks (the monolignols), whose modification through hydroxylation and O-methylation modulates the chemical and physical properties of the lignin polymer. The enzyme caffeic acid O-methyltransferase (COMT) is central to lignin biosynthesis. It is often targeted in attempts to engineer the lignin composition of transgenic plants for improved forage digestibility, pulping efficiency, or utility in biofuel production. Despite intensive inves… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
138
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(147 citation statements)
references
References 55 publications
9
138
0
Order By: Relevance
“…In comparison, perennial ryegrass (L. perenne) CAOMT (LpOMT1) showed ca. 7-fold greater activity against CaAlc compared with 5-HFA (Louie et al 2010). However, wheat (T. aestivum) CAOMT (TaCM) has a strong activity only towards 5-HCAld, but only small activities against other substrates, such as CA, CaAld, CaAlc, and 5-HCAlc (Ma and Xu 2008).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In comparison, perennial ryegrass (L. perenne) CAOMT (LpOMT1) showed ca. 7-fold greater activity against CaAlc compared with 5-HFA (Louie et al 2010). However, wheat (T. aestivum) CAOMT (TaCM) has a strong activity only towards 5-HCAld, but only small activities against other substrates, such as CA, CaAld, CaAlc, and 5-HCAlc (Ma and Xu 2008).…”
Section: Discussionmentioning
confidence: 99%
“…The enzyme activity for 5-HCAld was rather low, which was in sharp contrast to those of dicotyledonous CAOMTs whose function is in fact CAldOMT (Li et al 2000;Umezawa 2010). In contrast, perennial ryegrass (Lolium perenne) CAOMT (LpOMT1) showed the highest V max K m −1 for 5-HCAlc (relative activity, 100) followed by 5-HFA and CA (5.4 and 3.5, respectively; Louie et al 2010). For wheat (Triticum aestivum L. cv.…”
mentioning
confidence: 99%
“…The higher expression level of PAL in leaf suggested leaf might be the main organ for synthesizing the precursor of ferulic acid, and the higher expression level of the downstream enzyme COMT-1 and COMT-2 in rhizome suggested that ferulic acid might be synthesized and stored in rhizome, which was the major medical part of L. chuanxiong and contained high content of ferulic acid. The existence of two COMTs in L. chuanxiong was probably owing to the fact that COMTs were codified by a multigene family in plants (Louie et al 2010;Toquin et al 2003).…”
Section: Discussionmentioning
confidence: 99%
“…The initial structure model was solved by molecular replacement using the well-defined caffeic acid 3-O-methyltransferase structure (Zubieta et al, 2002) and refined to a resolution of 2.4 Å (see Supplemental Table 2 online). Similarly to the previously characterized plant phenolic O-methyltransferases (Zubieta et al, 2002;Louie et al, 2010), MOMT3 forms a homodimer, and each monomer consists of a large C-terminal catalytic domain involved in SAM/SAH and phenolic substrate binding and a small N-terminal domain that primarily mediates dimerization (Figure 2A). The N-terminal domain also contributes to the formation of the active site of the dyad molecule by providing residues (Met-26 and Ser-30) lining the back wall of the substrate binding cavity and helping enclose the recognition surface (Figures 2A and 2B).…”
Section: Crystal Structure Of Momt3 and Improvement Of Its Catalytic mentioning
confidence: 99%